The Concept of Influencing, Empowering, and Politics in Organizations (International Journal of Education and Literature, 2025)
This research is motivated by the complex phenomena that occur within modern organizations, where the dynamics of power, influence, and empowerment often determine work behavior and leadership effectiveness. In many organizations, poorly managed internal politics can lead to conflict, injustice, and decreased work motivation, whereas empowerment and ethical leadership can foster a highly competitive and collaborative culture. Based on this reality, the study aims to deeply analyze how the concepts of influencing, empowering, and organizational politics interact and affect the dynamics of work behavior, as well as to identify leadership strategies capable of managing organizational politics positively while creating an effective empowerment system for all members. The research employs a qualitative descriptive method using secondary data obtained through a literature review of various academic sources, scholarly journals, and previous relevant studies. The results show that organizational success largely depends on a leader's ability to balance power and participation, control and freedom, as well as individual and collective interests. The application of leadership strategies grounded in ethics, transparency, and empowerment has been proven to transform organizational politics into a positive force that enhances performance, loyalty, and trust among members. Thus, the integration of influence, empowerment, and organizational politics not only strengthens leadership effectiveness but also creates a productive, fair, and sustainable work environment.